SYSTEMATIC REVIEW METABOLIC DISRUPTION IN GESTATIONAL HYPERTENSION DISORDER - Diyas Windarena; Siti Nurharisah; Benigna Maharani; Mardiyono Mardiyono (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Gestational hypertension is one of the diseases responsible for increased morbidity and 18% of maternal deaths in the world. Gestational hypertension has complex causes and symptoms, so pathogenesis is difficult to determine. Complications of gestational hypertension will cause Preeclampsia. This study aims to explain the metabolic disorders experimented by women with gestational hypertension. This description can be used as an early detection tool for hypertension so that complications can be prevented.Methodology: Searching articles for this research is done by searching in the google scholar, science direct and PubMed databases. Only full text and written by english will be included in this study. The keyword that is used “Risk Factor” or “Metabolic” and “Gestational Hypertension” or “Blood Pressure” or “Pregnancy Hypertension” with the year limit between 2009 – 2019. A systematic review of PRISMA was used in this study. The study focused on the discussion about gestational hypertension in pregnant women.Results: 12 research articles were foundit is known that pregnant women with gestational hypertension have serum calcium, magnesium, nitric oxide, vitamin D, cobalt and iodine which tend to be lower than normal pregnant women. Whereas cadmium levels tend to be high can stimulate oxidative stress which is able to worsen the condition leading to preeclampsia.Conclusion: Health checks on pregnant women can be used as a basis for screening and treatment. Methods of checking calcium levels that allow as medium for screening in detecting the severity of hypertension and predicting disease risk.